Optimizing TPACK in Economics English: A Textbook Analysis - Syafitri, Widya; Zaim, M; Ardi, Havid; Febria Sri Artika (International Journal of Language Pedagogy, 2024)
This study examines the effectiveness of English textbooks for economics in aligning with the Technological Pedagogical Content Knowledge (TPACK) framework, which integrates technology, pedagogy, and content knowledge to enhance language learning. Descriptive qualitative was applied in this study. The analysis focused on four English textbooks: Career Path: Banking, Career Path: Business English, General English Material for Economic Students, and English for Islamic Banking. The evaluation revealed several limitations in these textbooks, such as inadequate alignment with economic content, lack of clear target audience and instructional objectives, insufficient technology integration, and minimal opportunities for interactive and dynamic learning experiences. These deficiencies were found to delay the development of essential language skills, including grammar, pronunciation, and communication, which are crucial for academic and professional success in the field of economics and banking. Furthermore, the analysis highlighted the absence of diverse activities that connect language skills with real-world applications, limiting the students' ability to effectively apply their knowledge in relevant scenarios. The textbooks also lacked comprehensive instructional support for listening and writing skills, critical thinking, and digital literacy, which are vital components of a modern, technology-enhanced learning environment. The study suggests that a more tailored approach, incorporating the TPACK framework, is necessary to address these gaps. By fostering interactive and immersive learning experiences, future textbooks can better meet the specific needs of economics students, promote active participation, and enhance both linguistic competence and digital literacy skills in preparation for global economic challenges.